Public Governance Principles in General Education School Management of Latvia - Rečs, Normunds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In contemporary world the effect of globalisation and information technologies cause transformational processes of states` public management that promote the application of new managament approaches and principles in public institution management.The changes in the public managament have effected and still effects processes of management also in education. The increase of school autonomy, a stronger focus on the process of education and its results created the need to expand the application of contemporary public management principles also in the managament of education institutions. The main goal of the report is to analyze the principles of public management and their implementation in the management of comprehensive schools of Latvia in the context of public management of Latvia and the world, and education reforms.